Association of maternally inherited GNAS alleles with African–American male birth weight - ADKINS, RONALD M. (2010)
OBJECTIVE: Human birth weight variation has a significant genetic component and important clinical consequences. We performed a survey of single nucleotide polymorphisms (SNPs) in 14 candidate genes to identify associations with birth weight variation. METHODS: SNP variation was surveyed in 221 healthy African–American mother-newborn pairs. Genes were selected based on previous association with obesity-related traits, significant differences in circulating protein levels in low birth weight pregnancies or association with newborn size in model organisms or growth disorders in humans. Association was tested via multiple linear regression with adjustment for significant covariables. RESULTS: Under a dominant model SNP rs7754561 of ENPPI was significantly associated with birth weight. Among imprinted loci, maternal genotypes for SNP rs6026576 of GNAS were significantly associated with birth weight (additive and dominant models). This association was restricted to male offspring. Analyses that distinguished between alleles of paternal and maternal origin demonstrated that only maternally-transmitted alleles were associated with birth weight and that this association was restricted to male newborns. CONCLUSION: The effect of only maternally-transmitted alleles of GNAS may be a consequence of the complex splicing and imprinting pattern of the GNAS gene, although the reason this effect is observed only among male newborns is unclear.